Annual variation in air-gulping behaviour in two Indian siluroids, Heteropneustes fossilis and Clarias batrachus - MAHESWARI, RENU; PATI, ATANU KUMAR; GUPTA, SEEMA (The Indian Journal of Animal Sciences, 2012)
Annual variation in air-gulping behaviour was studied in 2 Indian siluroids, Heteropneustes fossilis and Clarias batrachus. Air-gulping activity was examined 4 times every month in both species kept under an artificial LD 12:12 schedule for 15 months. A statistically significant annual rhythm in the rate of air-gulping activity was validated in both H.fossilis and C. batrachus. Over the seasonal time scale air-breathing activity raised during a long period characterized sequentially by a phase of initial oxygen depletion in the environment accompanied by higher temperatures (summer) and another phase that comprising a fully oxygen saturated watery environment (rains) when both H.fossilis and C. batrachus undertake vigorous energy demanding reproductive activities. Furthermore, it seems probable that in these fishes the daily rhythm in airgulping activity culminates in such a way into an annual rhythm that in both species while air-gulping activity is totally independent of DO over the daily time scale it may be partially DO dependent over the annual seasonal time scale. In summary, multi-frequency rhythm in air-gulping behaviour seems to strengthen the survival fitness of these tropical/ subtropical siluroids.